Opportunity profile for Digital Climate Advisory and Bundled Services (DCAS+) - Lower Mekong Basin, Cambodia - Giles, James; Soksophors, Yim; Vu Thi, Ngoc Bich; Phanith, Chou; Kong, Heng; Chanborey, Bora; Khieng, Phanna; Bunthoeun, Phen; Raksa, Sok; Swaans, Kees (2024)
The opportunity profiles provide a comprehensive view of the current Digital Climate Advisory Services (DCAS+) landscape by synthesizing findings from extensive studies in Cambodia. These studies, using methods like interviews, surveys, and focus groups, identify climate risks and vulnerabilities in key agricultural value chains, map the digital tools and services available, and examine farmers' needs and openness to digital climate solutions. The research highlights the areas where DCAS+ can have the greatest impact by addressing gaps in service and expanding digital access. Ultimately, these insights offer a clear direction for enhancing DCAS+ to better support communities facing climate challenges in the Asian Mega Delta region.